2017 Twelfth International Conference on Ecological Vehicles and Renewable Energies (EVER) 2017
DOI: 10.1109/ever.2017.7935949
|View full text |Cite
|
Sign up to set email alerts
|

“Reducing the energy consumption for comfort and thermal conditioning in EVs”

Abstract: One of the biggest barriers towards large scale adoption of electric and plug-in hybrid cars is still range limitation due to limited storage capacity of electric batteries. The air conditioning system for passenger comfort and the thermal conditioning system (battery and powertrain) are main auxiliary consumers in EVs with respect to energy consumption. Therefore, the Horizon 2020 project "OPTEMUS" proposes to tackle this bottleneck by leveraging low energy consumption and energy harvesting through a holistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Thermoelectric (TE) devices for localized cooling have been studied and predicted to achieve 29% compressor power saving while meeting equivalent comfort compared to traditional HVAC system [138]. Due to the need of reducing thermal energy consumption in electric vehicles, approaches that are more complete have been introduced [20], [139]. Steiner and Mladek introduced an occupant centered holistic approach for reducing energy consumption including technologies of energy harvesting with photovoltaic cells and shock absorbers, and preconditioned battery as heat source [110].…”
Section: Other Technologiesmentioning
confidence: 99%
“…Thermoelectric (TE) devices for localized cooling have been studied and predicted to achieve 29% compressor power saving while meeting equivalent comfort compared to traditional HVAC system [138]. Due to the need of reducing thermal energy consumption in electric vehicles, approaches that are more complete have been introduced [20], [139]. Steiner and Mladek introduced an occupant centered holistic approach for reducing energy consumption including technologies of energy harvesting with photovoltaic cells and shock absorbers, and preconditioned battery as heat source [110].…”
Section: Other Technologiesmentioning
confidence: 99%
“…The most of researches related to the problems of thermal comfort testing refer to savings that can be achieved during the operation of AC system, in order to reduce fuel and electric energy consumption, i.e., to achieve more autonomy in vehicle movement [6][7][8][9][10]. The use of air conditioning system not only considerably improves the comfort during driving, but it also reduces the internal noise and the need for additional opening of the window.…”
Section: Introductionmentioning
confidence: 99%
“…Increased heating ventilation and air conditioning (HVAC) power consumption, coupled with reduced battery performance, leads to a range reduction of 40% to 70% at −20 • C compared to 20 • C [1,2]. In addressing this issue research has been focussed on the development of heat pump technologies as a more efficient mechanism to produce cabin heat [3][4][5]. Other research introduces the use of the heat pump to provide heat to the battery, thereby minimising the impact of cold temperatures [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…In Ahn's research, multiple levels of heat delivered from the motor were considered; however, these levels did not change dynamically through the drive cycle. Steiner et al [5] investigated the benefits of using a heat pump to extract heat from a pre-heated battery; while this resulted in a 48% reduction in HVAC energy consumption, it is not preferable as the increased battery storage temperature may have adverse effects on battery ageing [26]. Leighton et al proposed and demonstrated a heat pump system which was able to heat the battery and improved low temperature range by between 5.6% and 23.2% [6].…”
Section: Introductionmentioning
confidence: 99%